2017
DOI: 10.1039/c6nr09833a
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial thermal resistance and thermal rectification in carbon nanotube film-copper systems

Abstract: Thermal rectification occurring at interfaces is an important research area, which contains deep fundamental physics and has extensive application prospects. In general, the measurement of interfacial thermal rectification is based on measuring interfacial thermal resistance (ITR). However, ITRs measured via conventional methods cannot avoid extra thermal resistance asymmetry due to the contact between the sample and the thermometer. In this study, we employed a non-contact infrared thermal imager to monitor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…In Fig. 5, the H/K ratio is shown as a function of the anharmonicity parameter β for the case of total energy per particle equal to H/N = 1, with the number of particles N = 2 15 = 32768. The range β ≤ 0.1 is considered, which, as will be shown, is sufficient for our study; see Fig.…”
Section: A Characteristics Of the Initial Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Fig. 5, the H/K ratio is shown as a function of the anharmonicity parameter β for the case of total energy per particle equal to H/N = 1, with the number of particles N = 2 15 = 32768. The range β ≤ 0.1 is considered, which, as will be shown, is sufficient for our study; see Fig.…”
Section: A Characteristics Of the Initial Conditionsmentioning
confidence: 99%
“…Heat in materials is transferred mainly by phonons, and phononics is a rapidly growing field of knowledge at the intersection of physics, materials science, and nanotechnology, studying phonon en-ergy transport and its applications [7,8]. Major achievements in this field are the development of thermal transistors [9,10], thermal diodes [11][12][13][14][15], and thermal logic devices [16][17][18]. Such developments require a better theoretical and experimental understanding of anomalous thermal transport in miniature low-dimensional systems.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal rectification describes the phenomenon in which the thermal flow direction has a certain influence on the TC of the interface of two different materials. The underlying mechanism of thermal rectification at interfaces and the efforts to investigate a high‐performance thermal rectifier have been discussed in detail in many papers . Opposite heat fluxes were proved to produce different values of the ITR, and this phenomenon is more pronounced when the magnitude of flux is larger .…”
Section: Factors Influencing the Itrmentioning
confidence: 99%
“…Thus, typically the CNT-Cu composites exhibit structures somewhere between the simplified structures shown in Figure 7a and b. Production and properties of CNT based coatings on Cu, such as the one shown in Figure 7c are rarely reported, except for some exceptions (see, e.g., Duan et al, 2017). Due to the high density of some CNT macrostructures, another typical form of CNT-Cu produced by different Cu deposition methods, such as electrodeposition (Chen et al, 2018a) and physical vapour deposition (PVD) (Han et al 2018) is shown in Figure 7d.…”
Section: Structure Of Cnt-cu Compositesmentioning
confidence: 99%